Sociocultural Relevance of Communication Strategies of Adolescent Sexual and Reproductive Health Programmes in Mozambique: A Study of Programa Geraçao Biz Activities in Nampula Province - da Silva, Lurdes (Afrika Focus, 2020)
Adolescent sexual and reproductive health (ASRH) challenges in Mozambique include early marriages, early pregnancies and HIV/AIDS. In 1999 the Programa Geração Biz (PGB) was created to address youths’ problems and improve their sexual and reproductive health (SRH). However, studies show Mozambican youths continue to be exposed to risks related to their SRH. Mozambique is a multicultural country but only 40% of Mozambicans speak Portuguese, the official language, while 93.5% of the population uses a Bantu language as their mother tongue. This raises an important issue – should PGB communication strategies (CS) take into account the country’s complex cultural reality? Studies recognise the role of culture in enhancing effective delivery of communication programmes. Concurrently, studies point to a lack of research analyzing CS of health campaigns. This paper’s aims are: (i) to examine PGB communication strategies; (ii) identify cultural challenges to these strategies; and (iii) determine the implications of these impediments for the PGB. Research methods included non-participant observation, in-depth interviews and focus group discussions. Research questions were based on the McGuire Communication/Persuasion Model, and data analyzed thematically using Nvivo Pro11. Results revealed the following: (i) interpersonal methods are used to deliver preventive messages, with sociocultural approaches often ignored or not used to reduce cultural barriers; (ii) cultural challenges identified include initiation rites, taboos surrounding sexuality, language and health terminologies, and parents’ attitudes towards early marriages; and (iii) these factors hinder effective delivery of programme messages. The conclusion is that the CS used by PGB does not sufficiently take into account the Mozambican sociocultural context. Taboos around sexuality have silenced open communication in this regard. Ideas of sexual abstinence, condom use and campaigns against early marriage stand in opposition to certain orientations of traditional initiations. KEY WORDS: COMMUNICATION STRATEGIES, SEXUAL AND REPRODUCTIVE HEALTH, PROGRAMA GERAÇÃO BIZ, McGUIRE’S COMMUNICATION/PERSUASION MODEL, CULTURAL CHALLENGES